Employer branding for the hospitality and tourism industry : finding and keeping talent - Gehrels, Sjoerd (Emerald Publishing, 2019)
This book explores the concept of Employer Branding (EB) as applied to the hospitality sector. Employer branding aims to assist businesses in becoming the employer of choice for potential employees. As such, the concept has potential to change classical approaches of managing people and to improve opinions on careers in the hospitality sector.